The organisation of the preventative and curative medical services and hospital and laboratory systems under a Ministry of Health (London : Co-operative Printing Society)
1919 1919 1910s 18 pages 18. TREATMENT CENTRES. — In every town of less than about 6,000 inhabitants and in certain selected village centres, there should be receiving stations comprising a well-equipped surgery or treatment centre, a staff of district nurses, and two, three, or four beds for the reception of acute cases and accidents, and of cases requiring careful observation for a day or two only. Patients should be transferred from receiving stations to the nearest cottage or county hospital when their condition renders it advisable, and with as little delay as possible. 19. At each hospital, whether county or local, there should be a sufficient number of consulting rooms to accommodate the local general practitioners using them. There should be special departments for all classes of cases which it is deemed best to deal with separately, such as school children, infants, mothers, tuberculosis and venereal diseases. 20. Special maternity wards or hospitals should be available for all patients whose home conditions render confinement unusually dangerous, or who require operative treatment of a major character. 21. In areas where it is necessary there should be well-equipped treatment centres in close touch with the hospitals. 22. All county hospitals, cottage hospitals, and other institutions within the National Health Scheme should be linked up with the national hospitals, and form part of an extended system of medical education. 23. There should be an ample service of ambulance cars for the easy transference of patients by road or rail from one hospital to another, and a good service of motor cars for the use of general practitioners, consultants, and specialists. 24. FREE CHOICE OF DOCTORS. — The general practitioners should work in groups round a hospital or treatment centre, the size of each group ranging from four to 20, according to the needs and distribution of the population. 25. No practitioner should be called upon to have under his charge more than 3,500 persons in urban districts, or 2,000 in rural districts. 20. All inhabitants within the area administered by any one group of medical practitioners shall be entitled to choose any practitioner within that group as his medical attendant, provided always that it does not involve the practitioner exceeding the allotted number of persons under his charge. 27. LABORATORIES. — Every county hospital should have well-equipped and staffed clinical and pathological laboratories, to the help of which for diagnosis and treatment every practitioner within the county should be entitled. 28. In addition to the county hospital laboratories there should be others attached to the larger cottage hospitals, so as to keep general practitioners in touch with laboratory methods, and to expedite the treatment of patients where such depends upon the results of laboratory investigation. 29. All laboratories should keep in touch and work in co-operation with one or other of the research departments connected with the national hospitals, and the work should be carried out not merely for the purposes of diagnosis and treatment, but as comprehensively as possible, having for its goal the nature, causation, and prevention of disease. 9 36/H24/6